Serum Uric Acid in Pre-eclampsia - Ajitkumar, Dr. Yanglem; Naorem, Dr. Sangeeta; Kshetrimayum, Dr. Victoria; Upen Singh, Dr. Yengkhom; Saha, Dr. Sneha; Devi, Dr. Potsangbam Jenny; Debbarma, Dr. Uma; Singh, Dr. Maisnam Amuba (International Journal of Innovative Research in Medical Science, 2019)
Background: Hypertension in pregnancy is a major cause of maternal death and also a major source of maternal and perinatal morbidity and perinatal morbidity. Hyperuricemia is a common finding in preeclamptic pregnancies. The elevation of uric acid in preeclamtic women often precedes hypertension and proteinuria, the clinical manifestations used to diagnose the disorder. The aim of this study is estimation of serum uric acid in preeclamptic patients. A case-control study was done in the Department of Biochemistry in collaboration with Deptt of Obstetrics & Gynaecology, Regional Institute Of Medical Sciences (RIMS), Impha(Manipur), India. Methods: Data collected from 50 pre-eclamptic pregnant women and 25 normotensive pregnant women admitted in antenatal ward, Deptt of Obstretics and Gynaecology, RIMS hospital. The blood samples were collected from these patients and analysed for serum uric acid level. Results: The serum uric levels were found to be significantly higher in preeclamptic cases than in normal controls. Mean±SD of uric acid was 8.82±1.68 mg% in cases compared to 4.06±0.96 mg% in the controls. Conclusion: Hyperuricemia can be used as biomarker for identifying women at risk of preeclampsia and its complications with adverse effects